AVM Management Equipoise Survey: physician opinions regarding the management of brain arteriovenous malformations. (6th December 2013) - Cockroft, Kevin M; Chang, Ki-Eun; Lehman, Erik B; Harbaugh, Robert E
Abstract : Introduction: Management of unruptured brain arteriovenous malformations (AVMs) is controversial, and conducting clinical trials in this area has been a challenge. We sought to determine which, if any, patient/AVM characteristics were most likely to influence clinicians' decisions regarding management and clinical trial enrollment. Methods: We performed an online survey (Survey Monkey) of members of the American Association of Neurological Surgeons (AANS) (n=4836) and Society of NeuroInterventional Surgeons (SNIS) (n=512). Physicians were asked to rate the likelihood that various patient/AVM characteristics would influence their treatment decisions and recommendations for clinical trial enrollment. 10 hypothetical case vignettes were also provided, and respondents were asked to select a management recommendation. Results: 277 (5.2%) responses were received. Characteristics that the majority (>50%) of respondents felt should lead to treatment included size <3 cm, superficial or cerebellar location, single draining vein, age <30 years, venous aneurysm, prior AVM hemorrhage, poorly controlled seizures, intranidal aneurysm, and patient's desire for treatment. However, a significant minority (>30%) felt that six of these same characteristics should lead to observation or should not influence treatment decisions. Characteristics that the majority (>50%) of respondents felt should lead to clinical trial enrollment included size > 6cm, deep or eloquent location, and age 51–70 years. The only characteristic that the majority felt should not lead to enrollment was the presence of an intranidal aneurysm. For the 10 vignettes, the majority of respondents (>50%) favored a specific course of management in only five cases. Conclusions: Clinicians' opinions on which patient/AVM characteristics are important for decisions regarding treatment or trial enrollment vary widely. These results suggest that there is no uniform opinion of clinical equipoise with regard to the management of brain AVMs.